Genetic aspects of chronobiologic rhythms in cardiovascular disease - Lemmer, Björn (From molecule to men, 2000)
Daily variations in the cardiovascular system are well documented from the carcadian rhythm in blood pressure and heart rate, pathophysiological events such as coronary infarction, angina pectoris down to the receptor-mediated processes of signal transduction. Telemetric data on blood pressure and heart rate profiles in animal models of human primary and secondary hypertension together with biochemical and molecular biological findings can help to get a better understanding of the mechanisms involved in the circadian organization of the cardiovascular system. From animal data of genetically different strains of rats (normotensive, hypertensive, transgenic hypertensive rats), we have good evidence that the master clock located in the nucleus suprachiasmaticus (SCN) is involved in the rhythmic organization. Chronopharmacological studies with different kinds of antihypertensive drugs also point to a genetically bound variation in the circadian pattern of blood pressure and its regulation.